WORK LIFE BALANCE DAN WORK ENGAGEMENT : DAMPAKNYA TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN - Latifah Nimas Sayekti; Suhartini (Jurnal Aplikasi Bisnis, 2022)
This study aimed to analyze the effects of WLB and WE on employee satisfaction with job satisfaction as an intervening variable at PT. Antam Tbk Head Office. The data collection method was questionnaires. The population of this study consisted of 321 employees, with a sample consisting of 178 employees. The data analysis method was Structural Equation Modeling (SEM) using SmartPLS v.3.0. The results of the study showed that, first, WLB has a positive effect on job satisfaction. Second, WE has a positive effect on job satisfaction. Third, WLB has a positive effect on employee performance. Fourth, WE has a positive effect on employee performance. Fifth, job satisfaction has a positive effect on employee performance. Sixth, WLB has a positive effect on employee performance through job satisfaction. Seventh, WE has a positive effect on employee performance through job satisfaction. The results of this study can be used as a reference for improving and maintaining WLB, WE, job satisfaction, and employee performance. Keywords: Work Life Balance, Work Engagement, Performance, and Satisfaction